Sosialisasi dan Implementasi Standar Operasional Prosedur (SOP) Kesehatan Keselamatan Kerja (K3) pada Praktikum Lapangan - Nurdiansyah, syarif Irwan (Lembaga Dongan Dosen, 2023)
Field practicum is one of the project-based learning activities (Project Base Learning), which makes students independent by learning directly from nature, in the field or in the community. The high risk of accidents and exposure to disease due to activities in the field has given rise to a control system, namely standard operating procedures (SOP) for occupational safety and health (K3), which are important to apply in every activity, especially in the laboratory or in the field. This community service activity (PKM) is to socialize and implement K3 SOPs in field practicum activities, to minimize risks during the activity, so that the learning process can run smoothly and achieve its goals. The activity was attended by 50 students participating in a combination of project-based courses in the Marine Science study program, with the delivery of material in lectures followed by practice in implementing K3 SOPs. Based on evaluations carried out before and after activities in the field, it shows an increase in the ability to understand K3 SOPs and all the impacts they cause.